Comparison of Two Different Retrograde Intrarenal Surgical Techniques: Is It Mandatory to Use Fluoroscopy During Retrograde Intrarenal Surgery? - Alma, Ergun; Ercil, Hakan (Urology Journal, 2019)
Purpose: To evaluate the efficacy and reliability of fluoroscopy-free retrograde intrarenal surgery. Materials and Methods: A retrospective evaluation was made of the data of 226 patients who underwent RIRS as kidney stone treatment between May 2015 and May 2017. When evaluation was made acccording to the exclusion criteria, the study continued with a total of 190 patients including 103 in whom fluoroscopy was used (Group 1) and 87 who underwent a fluoroscopy-free procedure (Group 2). Result: Group 1 patients comprised of 56 males and 47 females with a mean age of 41.5 ± 13.9 years. Group 2 patients comprised of 48 males and 39 females with a mean age of 42.6 ± 15.2 years. The mean stone size was 14.3 ± 2.7 mm in Group 1 and 14.1 ± 2.8 mm in Group 2. The mean operating time was calculated as 63.6 ± 8.2 minutes in Group 1 and 65.7 ± 9.7 minutes in Group 2. In Group 1, the success rate was determined as 83.5% on postoperative day 1 and as 92.2% in the postoperative first month. In Group 2, these rates were 81.6% and 90.8% respectively. No statistically significant difference was determined between the groups in respect of stone size (P= .752), operating time (P = .108) and postoperative first day (P = .732) and first month success rates (P = .724). Conclusion: Fluoroscopy-free RIRS is a surgical technique with a high rate of success that can be applied safely to be able to protect patients at high risk of radiation and the surgical team, particularly in centers with high patient circulation..